Extraction Of Defensin Antimicrobial Peptide From SWISS-PROT Database Using Extended Boyer-More Algorithm. - Ahamed Hassain Malim, N.H.; Zainol, Zurinahni (2007)
Antimicrobial Peptide (AMP) is a subset of protein that plays an essential role in innate immunity system. Researches on AMP are actively conducted in Immunology field where synthetics antibiotics are being developed. There are several classifications of AMP's families with different mechanism in immobilizing pathogens. Thus,-family classification could help speed up a search for specific family AMP.